Pengaruh Penggunaan Shopee Paylater dan Hedonic Shopping Motivations Terhadap Perilaku Konsumtif pada Generasi Z di Jakarta - Maylafaidza Putri Natasya; Corry Yohana; Ivan Purtano (Indo Publishing, 2026)
The growth of digital financial services, particularly Buy Now Pay Later (BNPL) such as Shopee PayLater, has significantly changed consumption patterns among Indonesia's Generation Z, with total PayLater debt reaching IDR 29.59 trillion by April 2025 and Gen Z accounting for nearly 40% of users. This consumer behavior is driven not only by easy access to digital credit but also by hedonic shopping motivations. This quantitative explanatory study aims to examine the partial and simultaneous effects of Shopee PayLater usage and hedonic shopping motivations on consumptive behavior among Generation Z in Jakarta. Data were collected through online questionnaires from 190 respondents using purposive sampling, analyzed with multiple linear regression using SPSS. The results show that Shopee PayLater usage has a positive and significant effect on consumptive behavior (regression coefficient 0.844, p = 0.000). Hedonic shopping motivations also have a positive and significant effect (coefficient 0.468, p = 0.000). Simultaneously, both variables significantly influence consumptive behavior (F = 414.913, R² = 0.816), explaining 81.6% of its variation. The study recommends integrating financial education features into BNPL platforms, strengthening regulations responsive to young consumers' psychological behavior, and developing digital financial literacy curricula that enhance self-control in shopping.